Life of Nian - Chan, Shu Xian (Nanyang Technological University, 2022)
Life of Nian is a short film that uses puppeteering to tell the story of a young Nian, the traditional lion dance costume reimagined as a native animal, surviving in modern Singapore. Shot in a documentary style, this film follows the daily life of Nian, and challenges he has to face as a stray.